Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

answer, please. I need help.

Answer Please I Need Help class=

Sagot :

irspow

Answer:

Step-by-step explanation:

[tex]\text{rule }(x^a)(x^b)=x^{(a+b)}\\ \\ (b^{-7})(b^3)=b^{(-7+3)}\\ \\ b^{-4}=\frac{1}{b^4}[/tex]

Answer:

1/ b^4

Step-by-step explanation:

because -7 +3 = -4 but it can only be positive. So you but the -4 to the bottom to become b^4